2005
DOI: 10.1196/annals.1338.057
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Inhibits ROS Formation and Apoptosis in Methylglyoxal‐Treated Human Hepatoma G2 Cells

Abstract: Methylglyoxal (MG) is a reactive dicarbonyl compound endogenously produced mainly from glycolytic intermediates. Elevated MG levels in diabetes patients are believed to contribute to diabetic complications. MG is cytotoxic through induction of apoptosis. Curcumin, the yellow pigment of Curcuma longa, is known to have antioxidant and anti-inflammatory properties. In the present study, we investigated the effect of curcumin on MG-induced apoptotic events in human hepatoma G2 cells. We report that curcumin preven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
57
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(63 citation statements)
references
References 17 publications
(21 reference statements)
4
57
0
Order By: Relevance
“…[12][13][14][25][26][27][28] The anti-tumor role of MG may also be attributed to its effects on cell migration. 15 Our results showing that MG inhibited the viability, proliferation, migration, and invasion of DLD-1 and SW480 colon cancer cells while promoting their apoptosis are in accordance with previous results in other cancer types.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[12][13][14][25][26][27][28] The anti-tumor role of MG may also be attributed to its effects on cell migration. 15 Our results showing that MG inhibited the viability, proliferation, migration, and invasion of DLD-1 and SW480 colon cancer cells while promoting their apoptosis are in accordance with previous results in other cancer types.…”
Section: Discussionmentioning
confidence: 99%
“…15 Our results showing that MG inhibited the viability, proliferation, migration, and invasion of DLD-1 and SW480 colon cancer cells while promoting their apoptosis are in accordance with previous results in other cancer types. [12][13][14][25][26][27][28] There are multiple potential mechanisms by which MG may induce tumor suppression: (1) inhibition of the synthesis of proteins and nucleic acids via irreversible modification of protein, DNA, and RNA;…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pro-oxidative effect of curcumin was observed in another study where curcumin at low concentrations reduced ROS formation in human myeloid leukemia cells and Hepatoma G2 cells, but elevated ROS levels at higher concentrations (7,8). In contrast, curcumin, as an anti-oxidant, inhibits ROS formation and apoptosis in human Hepatoma G2 cells and Chang liver cells ONCOLOGY REPORTS 23: 397-403, 2010 397 Curcumin induces apoptosis in human lung adenocarcinoma A549 cells through a reactive oxygen species-dependent mitochondrial signaling pathway (9,10). However, the precise signaling pathways for the ROS-mediated mitochondrial apoptotic cell death triggered by curcumin still remains unclear, especially in lung cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…Curcumin, isolated from turmeric (Curcuma longa L.), contains curcumin as a major component but also contains demethoxycurcumin (DMC) and bisdemethoxycurcumin (BDMC), respectively (4). Extensive research during the last half century has revealed several important functions of curcumin such as antioxidant, anti-inflammatory and anticancer properties (5)(6)(7). Recently, more and more studies have demonstrated the stronger activity of DMC when compared with curcumin in many aspects (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%